2018
DOI: 10.2147/jir.s155903
|View full text |Cite
|
Sign up to set email alerts
|

Systemic low-grade inflammation in post-traumatic stress disorder: a systematic review

Abstract: Studies examining post-traumatic stress disorder (PTSD) have either emphasized a relationship between PTSD and a systemically pro-inflammatory state or identified a link between PTSD and chronic disease. The aim of this study was to evaluate the evidence for a relationship between individuals with PTSD and systemic low-grade inflammation that has been proposed to underlie chronic disease development in this population. The authors conducted a systematic review of the literature (January 2006 to April 2017) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
1
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(104 citation statements)
references
References 40 publications
(88 reference statements)
2
85
1
9
Order By: Relevance
“…However, this equilibrium can be lost by impairment of any of these systems. In this regard, NF-κB activation by low-grade inflammation can be especially relevant as it has been reported in virtually all chronic age-related diseases, from metabolic disturbances, like diabetes mellitus, obesity, and the metabolic syndrome, to neurodegenerative, musculoskeletal, renal, cardiovascular, pulmonary, intestinal, and even behavioural diseases (Rosa, Judas, Lopes, & Mendes, 2008;Scarpellini & Tack, 2012;Speer, Upton, Semple, & McKune, 2018;Zhu, Armstrong, Tchkonia, & Kirkland, 2014). Interestingly, ageing and age-related diseases have also been associated with impaired circadian expression of core-clock genes and CCGs and impaired SIRT1 activity (Kondratov, Kondratova, Gorbacheva, Vykhovanets, & Antoch, 2006;Musiek et al, 2018;Wang et al, 2018).…”
Section: The Circadian Clock System In Health and Molecular Mechanimentioning
confidence: 99%
“…However, this equilibrium can be lost by impairment of any of these systems. In this regard, NF-κB activation by low-grade inflammation can be especially relevant as it has been reported in virtually all chronic age-related diseases, from metabolic disturbances, like diabetes mellitus, obesity, and the metabolic syndrome, to neurodegenerative, musculoskeletal, renal, cardiovascular, pulmonary, intestinal, and even behavioural diseases (Rosa, Judas, Lopes, & Mendes, 2008;Scarpellini & Tack, 2012;Speer, Upton, Semple, & McKune, 2018;Zhu, Armstrong, Tchkonia, & Kirkland, 2014). Interestingly, ageing and age-related diseases have also been associated with impaired circadian expression of core-clock genes and CCGs and impaired SIRT1 activity (Kondratov, Kondratova, Gorbacheva, Vykhovanets, & Antoch, 2006;Musiek et al, 2018;Wang et al, 2018).…”
Section: The Circadian Clock System In Health and Molecular Mechanimentioning
confidence: 99%
“…A number of reviews have also been published that discuss the inflammatory changes in a human PTSD model. In particular, articles investigated inflammation as observable through specific serum inflammatory markers that are known to be in association with PTSD [21,22] and conducted meta-analysis and meta-regression [23] as to summarize elevated systemic levels of oxidative stress and inflammation in individuals with PTSD as compared to healthy controls. However, reviews on the topic of inflammation and PTSD have demonstrated inconsistent findings, which have been suggested to be the result of the heterogeneity of the disorder.…”
Section: Introductionmentioning
confidence: 99%
“…A 2018 systematic review of literature explored the possible association between PTSD and low-grade inflammation. Speer, Upton, Semple, and McKune (2018) found evidence for the presence of inflammatory biomarkers that were elevated across included studies in the varied PTSD groups but not in the control groups.…”
Section: Ptsd As a Neuroinflammatory Contributormentioning
confidence: 92%